Humorous advertising used on TV: The effects of this appeal upon brand awareness - Ewing, Glen Kingsley (2009)
The following study is a detailed account of the effects humorous TV advertising has upon brand awareness. The objective of this study is to uncover firstly, can humour gain attention for the brand and through using humour in TV ads, can this create more recognition towards the brand? Also is the brand remembered in conjunction with the humorous TV advert? These are the main questions that will be studied and answered. A brief introduction to the study and the purpose of the study is explained and also a background to the topic area is identified.